2017
DOI: 10.1002/14651858.cd000526.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating tuberculous pericarditis

Abstract: Background Tuberculous pericarditis can impair the heart's function and cause death; long term, it can cause the membrane to fibrose and constrict causing heart failure. In addition to antituberculous chemotherapy, treatments include corticosteroids, drainage, and surgery. Objectives To assess the effects of treatments for tuberculous pericarditis. Search methods We searched the Cochrane Infectious Diseases Group Specialized Register (27 Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 56 publications
(236 reference statements)
0
42
0
6
Order By: Relevance
“…The most important trial on the use of corticosteroid in tuberculous pericarditis, the IMPI trial, failed to show a significant effect on the composite of death, cardiac tamponade requiring pericardiocentesis or constrictive pericarditis 46. A recent Cochrane review on the interventions for treating tuberculous pericarditis suggested that in HIV-uninfected individuals, glucocorticoid probably reduce deaths from pericarditis (risk ratio (RR) 0.39, 95% CI 0.19 to 0.80), even though there was no significant effect on all-cause mortality (RR 0.80, 95% CI 0.59 to 1.09) and the need for repeat pericardiocentesis (RR 0.85, 95% CI 0.70 to 1.04) 47. In people infected with HIV, corticosteroids did not significantly reduce the occurrence of pericardial constriction (RR 0.55, 95% CI 0.26 to 1.16), the need for repeat pericardiocentesis (RR 1.02, 95% CI 0.89 to 1.18) and all-cause mortality 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important trial on the use of corticosteroid in tuberculous pericarditis, the IMPI trial, failed to show a significant effect on the composite of death, cardiac tamponade requiring pericardiocentesis or constrictive pericarditis 46. A recent Cochrane review on the interventions for treating tuberculous pericarditis suggested that in HIV-uninfected individuals, glucocorticoid probably reduce deaths from pericarditis (risk ratio (RR) 0.39, 95% CI 0.19 to 0.80), even though there was no significant effect on all-cause mortality (RR 0.80, 95% CI 0.59 to 1.09) and the need for repeat pericardiocentesis (RR 0.85, 95% CI 0.70 to 1.04) 47. In people infected with HIV, corticosteroids did not significantly reduce the occurrence of pericardial constriction (RR 0.55, 95% CI 0.26 to 1.16), the need for repeat pericardiocentesis (RR 1.02, 95% CI 0.89 to 1.18) and all-cause mortality 47.…”
Section: Resultsmentioning
confidence: 99%
“…A recent Cochrane review on the interventions for treating tuberculous pericarditis suggested that in HIV-uninfected individuals, glucocorticoid probably reduce deaths from pericarditis (risk ratio (RR) 0.39, 95% CI 0.19 to 0.80), even though there was no significant effect on all-cause mortality (RR 0.80, 95% CI 0.59 to 1.09) and the need for repeat pericardiocentesis (RR 0.85, 95% CI 0.70 to 1.04) 47. In people infected with HIV, corticosteroids did not significantly reduce the occurrence of pericardial constriction (RR 0.55, 95% CI 0.26 to 1.16), the need for repeat pericardiocentesis (RR 1.02, 95% CI 0.89 to 1.18) and all-cause mortality 47. It is worth mentioning that all the studies included in this review were conducted in Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical drainage and pericardiectomy can been used where constriction or tamponade are detected. Open surgical drainage may be associated with less life-threatening re-accumulation requiring repeat pericardiocentesis in HIV negative patients [16]. Early pericardiectomy has been recommended to be of benefit to avert spread of inflammation to the myocardium and development of fibrosis and calcification of the pericardium [17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite low certainty in the evidence, adjuvant corticosteroids are conditionally recommended by the World Health Organisation (WHO) for people being treated for tuberculous pericarditis [19]. A recent systematic review found some evidence that corticosteroids reduced mortality amongst HIV-negative patients but had little association with constriction [16]. Much of the available evidence includes high proportions of people living with HIV who were untreated with antiretroviral therapy making conclusions difficult to generalise.…”
Section: Discussionmentioning
confidence: 99%
“…Once symptoms are present and imaging confirms chronic constriction then usually surgery is the only effective therapy 15 . Surgical pericardectomy is a complicated procedure with high morbidity and mortality reported in the literature.…”
Section: Introductionmentioning
confidence: 99%